From nothing : a theology of creation - McFarland, Ian A. (Ian Alexander), 1963- (Westminster John Knox Press, 2014)
Too often the doctrine of creation has been made to serve limited or pointless ends, like the well-worn arguments between science and faith over the question of human and cosmic origins. Given this history, some might be tempted to ignore the theology of creation, thinking it has nothing new or substantive to say. They would be wrong. In this stimulating volume, Ian A. McFarland shows that at the heart of the doctrine of creation lies an essential truth about humanity: we are completely dependent on God. Apart from this realization, little else about us makes sense. McFarland demonstrates that this radical dependence is a consequence of the doctrine of creatio ex nihilo, creation from nothing. Taking up the theological consequences of creation -- theodicy and Providence -- the author provides a detailed and innovative constructive theology of creation. Drawing on the biblical text, classical sources, and contemporary thought, From Nothing proves that a robust theology of creation is a necessary correlate to the Christian confession of redemption in Jesus Christ.